1988
DOI: 10.1007/bf00916947
|View full text |Cite
|
Sign up to set email alerts
|

Induction of circulating tumor necrosis factor (TNFα) as the mechanism for the febrile response to interleukin-2 (IL-2) in cancer patients

Abstract: Fever is frequently observed in cancer patients treated with high-dose recombinant human interleukin-2 (rIL-2). The preincubation of rIL-2 with polymyxin B, an antibiotic that inhibits the biologic effects of endotoxins, did not diminish the pyrogenicity of IL-2 in New Zealand rabbits, indicating that IL-2-induced fever is not due to contaminating endotoxins. In contrast to interleukin-1 (IL-1), tumor necrosis factor (TNF), and interferon alpha, which cause fever through their effects on arachidonic acid metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(66 citation statements)
references
References 28 publications
0
65
1
Order By: Relevance
“…In vitro, PMN can be activated by several agonists including cytokines such as TNF, GM-CSF and IL-8 as well as activation products of the complement system and in particular C5a (Slotman et al, 1986;Matsushima et al, 1989;Balkwill & Burke, 1989;Mantovani & Dejani, 1989;Tonnesen et al, 1984;Jacobs et al, 1980). These cytokines have been shown to be generated in vivo following IL-2 administration (Ward & Marks, 1989;Chong et al, 1989;Gemlo et al, 1988;Mier et al, 1988;Oppenheim, 1983). A recently published study by Mier and colleagues (Mier et al, 1990) showed that peak TNF levels occurred 2 h after IL-2 administration.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, PMN can be activated by several agonists including cytokines such as TNF, GM-CSF and IL-8 as well as activation products of the complement system and in particular C5a (Slotman et al, 1986;Matsushima et al, 1989;Balkwill & Burke, 1989;Mantovani & Dejani, 1989;Tonnesen et al, 1984;Jacobs et al, 1980). These cytokines have been shown to be generated in vivo following IL-2 administration (Ward & Marks, 1989;Chong et al, 1989;Gemlo et al, 1988;Mier et al, 1988;Oppenheim, 1983). A recently published study by Mier and colleagues (Mier et al, 1990) showed that peak TNF levels occurred 2 h after IL-2 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific molecular and cellular mechanisms of IL-2-mediated response and toxicity are not completely defined, IL-2 is known to result in a cascade of cytokines released at supraphysiologic levels in the body from IL-2-activated cells. This can result in a well-described capillary leak syndrome and eventual end-organ dysfunction [15][16][17][18][19][20][21][22][23][24][25][26][27]. The hallmarks of this "cytokine storm", are remarkably similar to the shock syndrome associated with bacterial septicemia, and include: sustained hypotension, tachycardia and increased vascular permeability.…”
Section: Early Physiology Investigations Of High Dose Il-2 Therapymentioning
confidence: 99%
“…Early animal and human studies suggested a dose-response effect on both efficacy and toxicity [15][16][17]. Thus most of the early literature described alternative methods of managing these patients than those used for sepsis, as the desirable therapeutic effects were thought to be linked to the toxicity (5)(6)(7)(8)(24)(25)(26)(27) and the inciting factor (IL-2 administration) was within the physician's control.…”
Section: Early Physiology Investigations Of High Dose Il-2 Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact mechanisms by which IL-2 mediates the increase in vascular permeability are largely unknown. Some authors have demonstrated a direct effect of IL-2 in vitro on vascular permeability (Fairman et al, 1987;Downie et al, 1992), whereas others have suggested that IL-2 exerts this effect by induction of various cytokines (Mier et al. 1988;Fraker et al, 1989;Edwards et al, 1992) such as tumour necrosis factor alpha (TNF-m) ['5I]uptake by the thyroid gland.…”
mentioning
confidence: 99%